A Review of Geopolymer Bricks and Concrete Containing Fly Ash and Palm Oil Fuel Ash - TAN, JIREH; Jamellodin, Zalipah (Recent Trends in Civil Engineering and Built Environment, 2022)
The production of conventional bricks and concrete will involve the emission of greenhouse gases. Fly ash (FA) and palm oil fuel ash (POFA) as the industrial byproduct or waste material are potentially to be used to replace the existing conventional construction materials through the process of geopolymerization. These waste materials can be used as a raw material to produce construction materials which will reduce the negative impact on our environment and also reduce the disposal of waste materials as an environmental pollutant. A study is conducted to review the physical properties, microstructure and performance (compressive strength and water absorption) of eco-friendly bricks and concrete made from FA and POFA through geopolymerization. In the journal review, all the study will be summarized according to the waste material used, alkaline activator, specimen size, curing condition, conducted test and author.